Food microbiology - Adams, Martin R.; McClure, Peter J.; Moss, Maurice O. (London : Royal Society of Chemistry, 2024)
Comprehensive, updated textbook covering interactions between micro-organisms and food$1 (Bspoilage, foodborne illness, fermentation, and quality control$1 (Bdesigned for students in biological sciences, biotechnology, and food science, as well as researchers and practitioners.s
In English
Keywords: Food microbiology -- Textbooks; Food microbiology -- Research; Microbiology and food; Food science -- Microbiology